Modeling, measuring, and training teachers’ counseling and diagnostic competencies - Gerich, Mara; Trittel, Monika; Bruder, Simone; Klug, Julia; Hertel, Silke; Bruder, Regina; Schmitz, Bernhard (Competence assessment in education, 2017)
In their professional routines, teachers must perform highly complex and demanding tasks that require extensive counseling and diagnostic competence. There is a growing request for programs that foster these important teacher competencies in educational practice (e.g., German Society for Psychology, Psychologie in den Lehramtsstudiengängen: Ein Rahmencurriculum [Psychology in teacher education: A framework curriculum]. Retrieved from http://www.dgps.de/_download/2008/Psychologie_Lehramt_Curriculum.pdf, 2008) as well as a call for the theoretical modeling of competencies and approaches for their assessment in educational research (Koeppen et al., J Psychol 216:61-73, 2008). In the current research project we theoretically conceptualized and empirically validated specific models of teachers’ counseling and diagnostic competence for the domain of student learning behavior, and constructed several instruments for their assessment. Subsequently, we developed specific training programs on counseling and diagnostics for prospective and in-service teachers based on the models, and evaluated them by means of the specified instruments. We describe the results of the research project in this chapter and discuss future prospects for educational research and teacher training.